Scientific Evolution of Philosophical Concepts of the Origins of Universe and Life - de Souza Agostini, Cristina; Porto da Silveira, Isabel; Cardoso Polla, Cauê (Revista Archai, 2021)
In order to demonstrate the great importance of Philosophy in the elaboration of current scientific theories, a parallel was drawn between concepts of pre-Socratic Philosophy and current modern theories. Thus, throughout this essay, the convergences between some elaborations developed by philosophers and their reinterpretation from a scientific point of view, supported by the scientific method and the present technological apparatuses, were exposed. In this sense, having as its core the reflection about the atomic theory of Leucippus and Democritus, we investigate the way in which atomism dialogues with the modern Atomic Theory to the Quantum Theory, through concepts of Kosmos and Cosmology. In a second moment, origin of life theories were revisited from the pre- Socratic concepts of Psyche. Finally, Philosophy and Science are brought together as possible and complementary tools for the restoration of the amplification of thought and investigative processes.